Implementation of Quality Indicators of Perinatal/Neonatal Palliative Care One-Year Following Formal Training - Charlotte Wool; Elvira Parravicini (Frontiers Media S.A., 2021)
Objective: The aim of this study was to measure implementation of quality indicators (QIs) of Perinatal/Neonatal Palliative Care (PNPC) as reported by participants following a one-year training course.Study Design: A cross-sectional survey mixed-method design was used to obtain data from an interdisciplinary team of professionals one year after attending a PNPC training course. A questionnaire with 32 QIs queried participants about self-reported implementation of PNPC and that of their colleagues. Descriptive and frequency data were analyzed to measure the implementation of PNPC QIs. Qualitative data were examined using content analysis.Results: Response rate was 34 of 76 (44.7%). Half of the QIs are implemented in clinical settings by course attendees more than 90% of the time, and 15 QIs are implemented between 70 and 89.9%. Colleagues within the same healthcare system applied palliative care practices less frequently than those who attended the training course. When asked if quality indicators were "always" implemented by colleagues, the average difference in scores was 36% lower. Qualitative analyses resulted in three themes that addressed changes in clinical practice, and four themes that summarized barriers in practice.Conclusion: There is high frequency of implementation of QIs by professionals who attended an evidence based PNPC training course. PNPC is implemented by the colleagues of attendees, but with less frequency. Attending evidence-based education increases clinicians' opportunities to translate quality PNPC care into clinical settings.